Effects of COVID-19 Epidemic Lockdown on Postpartum Depressive Symptoms in a Sample of Italian Mothers - Spinola, Olivia; Liotti, Marianna; Speranza, Anna Maria; Tambelli, Renata (Frontiers in Psychiatry, 2020)
The extraordinary health emergency of the COVID-19 pandemic represents a new challenge for mental health researchers and clinical practitioners. The related containment measures may be a risk factor for psychological distress and mood disorders, especially in at-risk populations. This study aims to explore the impact of COVID-19 on postpartum depressive symptoms in mothers with children below 1 year of age. An online questionnaire survey was therefore conducted in Italy between May and June 2020. The survey consisted of several self-administered questionnaires: besides some ad-hoc questionnaires, the Edinburgh Postnatal Depression Scale (EPDS), the Scale of Perceived Social Support (SPSS) and the Maternity Social Support Scale (MSSS) were used. Two hundred forty-four Italian women participated in the study. The prevalence of postpartum depression symptomatology among mothers was 44%, as measured through the EPDS (cut-off >= 12). Women who spent the isolation in northern Italy adopted maladaptive coping strategies significantly more than women living in areas at lower risk. The analysis highlighted a significant difference between the group that was not directly affected by the virus and women who have had a direct or indirect contact with it. Besides situational factors specific to the pandemic, the results show that there are some risk factors tied to the personal history of the mother (e.g.: having had a previous abortion). These data should inform and enlighten future protocols of intervention.